PENGARUH PANJANG SERAT BAMBU PETUNG TERHADAP KEKUATAN MEKANIK DAN SIFAT FISIS KOMPOSIT YANG DISUSUN SECARA ACAK - Umam, Khotibul Umam; H.D, Adityo Nor setyo; Listyanda, R Faiz (POLITALA PRESS, 2024)
Natural fiber composites are increasingly being developed to substitute less environmentally friendly materials such as metal and fiberglass. Petung bamboo has the potential to be a substitute for glass fiber in polymer composite reinforcement because it has good fiber quality. This research aims to determine the effect of random fiber arrangement with variations in fiber length on mechanical strength. The composite was made using the hand lay-up method with fiber length variations of 5 mm, 10 mm, 15 mm, and 20 mm. The volume fraction of petung bamboo fiber is 30% soaked in 5% NaOH for 2 hours. The research results show that specimen C has the highest tensile strength and elastic modulus values ​​of 1.25 Kgf/mm^2 and 1.93 Kgf/mm^2. In contrast, specimen A has the lowest tensile strength and elastic modulus values ​​of 0.76 Kgf/mm ^2 and 1.14 Kgf/mm^2. The rich, void, and fiber pull-out matrix causes the mechanical strength of the composite to be less than optimal. The effect of adding petung bamboo fiber in the composite can increase the mechanical strength as the fiber length increases.